THE ROLE OF MOTHER LANGUAGE ON INDONESIAN ENLIGHTENMENT - Rina Devianty (VISION, 2018)
Mother tongue has a very important role in the mastery of Indonesian language. Mother tongue is the first language controlled by a child in the first year of life. At that time, speaking skill especially spoke, became the most appropriate means for the development of Indonesian language in preschoolers. Intensive communication between the child and the people around him greatly affects his ability to learn language. Mother tongues used at all times are often carried over to formal or official situations that should use good and proper Indonesian.Keywords: mother tongue, Indonesian